Influences of microgap and micromotion of implant–abutment interface on marginal bone loss around implant neck - Liu, Yang; Wang, Jiawei (Archives of oral biology, 2017)
•Elaborated respectively the influence mechanisms of the microgap and micromotion between the implant and the abutment on implant marginal bone loss in detail.•The relationship between microgap, micromotion, microleakage and mechanical damage, and their influences on bone resorption around implant neck are particularly explained.•Some feasible clinical methods to reduce the bone resorption engendered by the microgap and micromotion at the IAI are recommended. To review the influences and clinical implications of micro-gap and micro-motion of implant-abutment interface on marginal bone loss around the neck of implant. Literatures were searched based on the following Keywords: implant-abutment interface/implant-abutment connection/implant-abutment conjunction, microgap, micromotion/micromovement, microleakage, and current control methods available. The papers were then screened through titles, abstracts, and full texts. A total of 83 studies were included in the literature review. Two-piece implant systems are widely used in clinics. However, the production error and masticatory load result in the presence of microgap and micromotion between the implant and the abutment, which directly or indirectly causes microleakage and mechanical damage. Consequently, the degrees of microgap and micromotion further increase, and marginal bone absorption finally occurs. We summarize the influences of microgap and micromotion at the implant-abutment interface on marginal bone loss around the neck of the implant. We also recommend some feasible methods to reduce their effect. Clinicians and patients should pay more attention to the mechanisms as well as the control methods of microgap and micromotion. To reduce the corresponding detriment to the implant marginal bone, suitable Morse taper or hybrid connection implants and platform switching abutments should be selected, as well as other potential methods.